2007
DOI: 10.1111/j.1365-2133.2007.08162.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between exposure dose and response in induction and elicitation of contact hypersensitivity in humans

Abstract: Like all physiological systems, the human immune system exhibits dose-response relationships in its reactions. The strength of sensitization is related to the potency of the immunogen and the dose that reaches the immune system. In skin, as sensitizing dose per unit area (mug cm(-2)) is increased on a log scale, there is a sigmoid dose-response curve for subsequent reactivity. Similarly, the response to elicitation shows a classical sigmoid response to increasing challenge dose, with the dose per unit area aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 53 publications
4
82
0
3
Order By: Relevance
“…Within the field of contact sensitisation, the main factor considered to determine the extent of elicitation is the strength of the induction [30]. In addition, the stronger the degree of induction, the lower the dose that sensitised individuals will react to upon any recall challenge [12]. Furthermore, the evidence that the induction phase of T-cell memory is more susceptible to the effects of prolonged exercise than the elicitation phase [14] may also point towards the period where participants would have benefited most from a nutritional countermeasure such as COL. Biswas et al [35] did demonstrate that COL can differentially affect in vitro stimulation of human peripheral blood mononuclear cells by enhancing IFNγ production during weak antigenic stimulation but not under conditions of strong antigen stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the field of contact sensitisation, the main factor considered to determine the extent of elicitation is the strength of the induction [30]. In addition, the stronger the degree of induction, the lower the dose that sensitised individuals will react to upon any recall challenge [12]. Furthermore, the evidence that the induction phase of T-cell memory is more susceptible to the effects of prolonged exercise than the elicitation phase [14] may also point towards the period where participants would have benefited most from a nutritional countermeasure such as COL. Biswas et al [35] did demonstrate that COL can differentially affect in vitro stimulation of human peripheral blood mononuclear cells by enhancing IFNγ production during weak antigenic stimulation but not under conditions of strong antigen stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Topical skin exposure to novel antigens (contact sensitisation) such as diphenylcyclopropenone (DPCP) allows for the effects of systemic stressors on the induction and elicitation phases of in vivo T-cell-mediated immune response to be quantified by oedema and erythema [11][12][13]. By use of this model of experimental contact sensitisation, Harper-Smith et al [14] demonstrated that participation in a single bout of prolonged (2 h) moderate exercise compared to rest significantly reduced both the induction and the elicitation of in vivo cell-mediated immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the differences in the intensity of CHS response (measured as flank skin thickness) to DNCB and squaric acid dibutyl ester (SADBE) were associated with challenge doses (Scott et al, 2002). The increase in skin-fold thickness following challenge of humans or mice sensitized with increasing doses of DNCB, as well as the data that showed inverse correlation between the magnitude of sensitization dose and the dose needed to induce measurable response (Friedmann, 2007;Scott et al, 2002) demonstrated the contribution of sensitization to the intensity of CHS. Although these studies clearly demonstrated the contribution of sensitization to the intensity of CHS expression, the underlying mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…One of the approaches in studying ACD in humans is elucidation of the dose-response relationships between the induction and elicitation phases of the reaction; these seem to determine the incidence as well as intensity of an ACD response (Friedmann and Moss, 1983;Friedmann, 2007). A quantitative relationship between the concentrations used for sensitization and elicitation of the allergic response to dinitrochlorobenzene (DNCB) was demonstrated both in humans (Friedmann and Moss, 1983;Friedmann, 2007) and mice (Scott et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation